Copolymerization of 4-Acetylphenyl Methacrylate with Ethyl Methacrylate: Synthesis, Characterization, Monomer Reactivity Ratios, and Thermal Properties - Barim, Gamze; Yayla, Mustafa Gokhun (Wiley, 2014)
Methacrylates have high glass transition temperature (Tg) values and high thermal stability. A new methacrylate copolymer, poly(4-acetylphenyl methacrylate-co-ethyl methacrylate) (APMA-co-EMA), was synthesized. The thermal behaviors of copolymers were investigated by differential scanning calorimetry and thermogravimetric analysis. They behaved as new single polymers with singleTg’s and the thermal stability of the copolymers increased with increasing 4-acetylphenyl methacrylate (APMA) fraction, leading to the manufacture of copolymers with desiredTgvalues. Structure and composition of copolymers for a wide range of monomer feed ratios were determined by Fourier transform infrared (FT-IR) and1H-nuclear magnetic resonance (1H-NMR) spectroscopic techniques. Copolymerization reactions were continued up to 40% conversions. The monomer reactivity ratios for copolymer system were determined by the Kelen-Tüdös (ra(APMA)=0.81;rb(EMA)=0.61) and extended Kelen-Tüdös (ra=0.77;rb=0.54) methods and a nonlinear least squares (ra=0.74;rb=0.49) method.
Keywords: Chemical technology; TP1-1185